Whites excrete a water load more rapidly than blacks - Weder, Alan B; Gleiberman, Lillian; Sachdeva, Amit (Hypertension (Dallas, Tex. 1979), 2009)
A recent report demonstrated a racial difference in response to furosemide compatible with increased ion reabsorption in the thick ascending limb of the loop of Henle in blacks. Urinary dilution is another function of the loop-diuretic-sensitive Na,K,2Cl cotransporter in the thick ascending limb, and racial differences in urinary diluting capacity have not been reported previously. We assessed diluting segment (cortical thick ascending limb and distal convoluted tubule) function in black and white normotensives in 2 studies using a water-loading approach. In both studies, we found that whites excreted a water load more rapidly than blacks. In the first study, the final free water clearance rates (mean+/-SD) were 7.3+/-4.7 mL/min in whites (n=17, 7 females and 10 males) and 3.8+/-3.6 mL/min in blacks (n=14, 9 females and 5 males; P<0.03). In the second study, final free water clearance rates were 8.3+/-2.6 mL/min in whites (n=17, 8 females and 9 males) and 6.4+/-1.8 mL/min in blacks (n=11, 8 females and 3 males; P<0.01). We found no evidence of a racial difference in renal proximal tubular fluid reabsorption as assessed by renal endogenous lithium clearance or in plasma vasopressin level that could explain the difference in free water excretion. We conclude that our observations are most consistent with a lower capacity of ion reabsorption in the renal diluting segment in blacks. Slower excretion of an acute water load may have been an advantage during natural selection of humans living in arid, hot climates.